Social top-down response modulation (STORM): a model of the control of mimicry in social interaction - Wang, Yin; Hamilton, Antonia F. de C. (Frontiers, 2012)
As a distinct feature of human social interactions, spontaneous mimicry has been widely investigated in the past decade. Research suggests that mimicry is a subtle and flexible social behavior which plays an important role for communication and affiliation. However, fundamental questions like why and how people mimic still remain unclear. In this paper, we evaluate past theories of why people mimic and the brain systems that implement mimicry in social psychology and cognitive neuroscience. By reviewing recent behavioral and neuroimaging studies on the control of mimicry by social signals, we conclude that the subtlety and sophistication of mimicry in social contexts reflect a social top-down response modulation (STORM) which increases one's social advantage and this mechanism is most likely implemented by medial prefrontal cortex (mPFC). We suggest that this STORM account of mimicry is important for our understanding of social behavior and social cognition, and provides implications for future research in autism.